Multiple stabilizing pathways in wetland plant communities subjected to an elevation gradient. (September 2019) - Fu, Hui; Yuan, Guixiang; Jeppesen, Erik; Ge, Dabing; Zou, Dongsheng; Lou, Qian; Dai, Taotao; Li, Wei; Zhong, Jiayou; Huang, Zhenrong; Liu, Qiaolin; Wu, Aiping
Graphical abstract: Highlights: Diversity, dominance, asynchrony and abundance can control stability. Generalized multilevel path models clarify the multivariate relations. Selection and insurance effects exerted a dominated control over stability. Dominance rather than diversity mediated indirect effects of elevation on stability. The four stabilizing pathways interactively operated along elevation gradients. Abstract: Understanding how ecological processes mediate community stability as a response to variation in the environment is a central goal in ecology. Four biotic mechanisms – portfolio, selection, insurance, and over-yielding effects – have been suggested to control community stability. While the significance of each of these mechanisms is debated, few studies have elucidated changes in their relative importance along environmental gradients. We used six years of field observations from a natural assembled wetland plant community to explore how stability changed directly or indirectly along an elevation gradient. All four mechanisms mentioned above contributed significantly to the variation in temporal stability (totally 94%), with selection and insurance effects being most important. Generalized multilevel path modelling indicates that the four mechanisms destabilize individual populations and functional groups, even though they have significant stabilizing effects on community productivity. The modelling also suggests that community dominance rather than species diversity largely mediate the indirect effects of elevation on community stability. Increasing elevation indirectly affects stability through changes in community dominance, synchrony, and abundance. Although no significant responses of species diversity were found along elevation gradients, species diversity apparently controlled stability both directly and indirectly through changes in community dominance, synchrony, and abundance. Our study illustrates that understanding the multivariate chains linking the direct, indirect, and interactive effects of elevation gradients on plant communities may help clarifying complex biotic stability mechanisms.